2021
DOI: 10.3390/ijerph18115749
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Factors Associated with Referral of Patients with Opioid Maintenance Therapy from Specialized Addictive Disorders Centers to Primary Care

Abstract: Background: One of the most important issues for opiate maintenance therapy efficacy is the involvement of primary care physicians (PCPs) in opiate use disorder treatment, especially after referral from specialized units. This study aimed to analyze the progress of subjects in a specialized center and after referral to PCPs. Methods: This study was an observational prospective study. Recruitment took place in a specialized addictive disorder center in western France. All patients were evaluated (sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…At the end of the second stage of rehabilitation physical training, Liu's overall strength quality was significantly improved. 6 The bench press score was improved to the personal all-time best score of 140 kg at the 14th week after surgery, and finally reached 150 kg; 8 super groups of pull-ups (6 for each group) and flexor arm support (8 for each group) with 32kg weight; Complete 10 times with 55 kg high turn. Hard 160 kg, nearly 2 times the weight; Box squat weight 100 kg, each group of 4, can be completed in two consecutive groups; Rome chair lifting 10 kg, complete 20, a total of 6 groups; Shoulder on the bench load hip sprint, can be in fast circumstances, load 80 kg, 12, 6 groups; Under the condition of timing, 25 barbell pieces can be completed, a total of 6 groups.…”
Section: Discussionmentioning
confidence: 93%
“…At the end of the second stage of rehabilitation physical training, Liu's overall strength quality was significantly improved. 6 The bench press score was improved to the personal all-time best score of 140 kg at the 14th week after surgery, and finally reached 150 kg; 8 super groups of pull-ups (6 for each group) and flexor arm support (8 for each group) with 32kg weight; Complete 10 times with 55 kg high turn. Hard 160 kg, nearly 2 times the weight; Box squat weight 100 kg, each group of 4, can be completed in two consecutive groups; Rome chair lifting 10 kg, complete 20, a total of 6 groups; Shoulder on the bench load hip sprint, can be in fast circumstances, load 80 kg, 12, 6 groups; Under the condition of timing, 25 barbell pieces can be completed, a total of 6 groups.…”
Section: Discussionmentioning
confidence: 93%
“…The 6-month period was chosen since it is the time generally required to adapt and stabilize the dosage of OMT in the context of a global opioid use disorder treatment. In a previous study, we showed that PWUD with opioid dependence were clinically improved and stabilized in the first 6 months and 50% were referred within 280 days of entry into the center specialized in addictive disorders and the OMT introduction [ 50 ]. PWUD attending one of the 10 involved centers during the inclusion period, and corresponding to the inclusion criteria were proposed to participate to the study.…”
Section: Methodsmentioning
confidence: 99%
“…The International Statistical Classification of Diseases and Related Health Problems-10 (ICD-10) criteria align in general with DSM-5 ( Hasin et al, 2013 ). OUD may develop at opioid doses employed in prescription pain management ( McAuliffe, 2013 ; Minozzi et al, 2013 ; Campbell et al, 2015 ; Degenhardt et al, 2021 ), although the burden of prescription OUD in pain patients is difficult to estimate ( Guillou-Landreat et al, 2021 ; Hasin et al, 2022 ; Sullivan and Ballantyne, 2022 ).…”
Section: Introductionmentioning
confidence: 99%